The Effect of Implementing PSAK 72 on Financial Performance and Shareholders Value at the Property Company Registered on the IDX for the 2018-2020 Period - Simanjuntak, Nathalina Br; Siringoringo, Magdalena Judika Br; Manurung, Amran (AKADEMIK: Jurnal Mahasiswa Humanis, 2024)
This research aims to determine the effect of implementing PSAK 72 regarding revenue recognition from contracts with customers on financial performance and shareholder value in property companies listed on the IDX for the 2018-2020 period. This research uses quantitative research, namely research that emphasizes the objective measurement aspect of social phenomena. The sampling method used in this research is nonprobability sampling and the sampling technique used is purposive sampling. This research data is secondary data obtained directly from the Indonesia Stock Exchange website for the 2018-2020 period. Where the data taken from annual reports and company financial reports is quarterly. The analysis method used is simple linear regression analysis. This research was carried out using IBM SPSS 22.0 software. The results of this research indicate that the implementation of PSAK 72 income recognition has a negative effect on financial performance. The results of this research also show that the implementation of PSAK 72 income recognition has a positive effect on shareholder value.